2012
DOI: 10.1007/s12070-012-0484-y
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Fine-Needle Aspiration in Head and Neck Lymphoma: A Cross-Sectional Study

Abstract: The objective of this paper was that fine-needle aspiration (FNA) has become a well-liked modality in the diagnosis, staging, and follow-up of head and neck masses. Limited studies exist regarding the value of FNA in the diagnosis of head and neck masses. We aimed to evaluate the diagnostic value of head and neck lymphomas. This cross-sectional study method was performed in Imam Hospital and Cancer Institute affiliated to Tehran University of Medical Sciences. In a 5 years period between January 2006 and June … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…It accelerates the assessment of cellular morphologic features of thyroid nodules from which the malignant risk can be determined. This information is important when planning the therapeutic management of nodules, deciding in followup of the nodule size, repeating the biopsy or performing a total or partial thyroidectomy [1,2]. Although FNAC is widely used in clinical diagnosis, cytologically indeterminate thyroid nodules continue to present a diagnostic challenge for pathologists.…”
Section: Introductionmentioning
confidence: 99%
“…It accelerates the assessment of cellular morphologic features of thyroid nodules from which the malignant risk can be determined. This information is important when planning the therapeutic management of nodules, deciding in followup of the nodule size, repeating the biopsy or performing a total or partial thyroidectomy [1,2]. Although FNAC is widely used in clinical diagnosis, cytologically indeterminate thyroid nodules continue to present a diagnostic challenge for pathologists.…”
Section: Introductionmentioning
confidence: 99%
“…The utility of FNAC for diagnosing lymphoma was reported in 47 studies 8‐54 . The pooled sensitivity and specificity of FNAC for diagnosing lymphoma were 93% (95% CI, 90%‐95%) and 97% (95% CI, 95%‐98%), respectively (Figures 3 and 4).…”
Section: Resultsmentioning
confidence: 93%
“…During the second screening stage, 47 studies with 7268 participants met the inclusion criteria and used in our analysis (Figure 1). 8‐54 …”
Section: Resultsmentioning
confidence: 99%
“…Although pathologists feel that FNA has limited efficacy in the evaluation of lymph nodes and lymphoma, its use is increasing. 20,22 Ancillary diagnostic techniques used in modern pathology practice such as immunohistochemistry and flow cytometry can be applied to standard cytology practice to improve the accuracy of lymphoma diagnosis. 22 In our study, 95.5% of the aspirates of head and neck swellings were from lymph node and despite the false negative cases, we feel that with the high specificity and predictive value, lymph node FNAC still has a major role in screening for lymphoma and avoiding unnecessary surgical biopsy for reactive adenopathy.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Various studies have compared results from FNAC and histology and found sensitivity and specificity ranging between 50% to 100%. [17][18][19][20][21] Although the incidence of FNAC use has increased, some studies raise questions regarding its accuracy and utility, especially in the diagnosis of lymphomas. 22 In the management of pediatric head and neck Swellings, several studies that compared FNAC preliminary diagnosis with the final definitive histological diagnoses have shown the usefulness of FNAC in terms of its high sensitivity and specificity and in avoidance of unnecessary surgical biopsies for benign lesions.…”
Section: Introductionmentioning
confidence: 99%